2015
DOI: 10.1080/ac.70.1.3064591
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin: a cardiometabolic marker associated with global cardiovascular risk

Abstract: ADPN might be considered a key component mediating the cross-talk between adipose tissue, cardiac cells and the vasculature. Accordingly, its routine measurement might become a new target in the management of global CV risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
(75 reference statements)
0
15
0
1
Order By: Relevance
“…Given the well-known beneficial effect of adiponectin on several metabolic and vascular phenotypes [ 4 , 38 40 ], the intrinsic biological nature underlying such deleterious effect(s) is difficult to understand or even only to speculate; otherwise, we would not be talking of “paradoxical effect/association”. Having acknowledge this, some deleterious actions of adiponectin on processes possibly involved in atherogenesis, including stimulatory effect on secretion of pro-atherogenic cytokines [ 41 43 ] and angiogenesis [ 42 , 44 ], have been recently reported in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-known beneficial effect of adiponectin on several metabolic and vascular phenotypes [ 4 , 38 40 ], the intrinsic biological nature underlying such deleterious effect(s) is difficult to understand or even only to speculate; otherwise, we would not be talking of “paradoxical effect/association”. Having acknowledge this, some deleterious actions of adiponectin on processes possibly involved in atherogenesis, including stimulatory effect on secretion of pro-atherogenic cytokines [ 41 43 ] and angiogenesis [ 42 , 44 ], have been recently reported in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Chiara and cols. (33) showed that subjects with low adiponectin levels had a higher prevalence of obesity, MetS, DM and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Среди них лептин ассоциирован с прогрессированием атеросклероза и худшим клиническим исходом, особенно у пациентов с ожирением, а адипонектин является сильным протективным фактором. Уровни адипонектина ассоциированы с эссенциальной гипертензией [82], риском развития CCЗ [19] и функцией сердца при бессимптомном диабете 2 типа [16]. Метаболическое воспаление может быть связано с изменением профиля циркулирующих адипокинов [131].…”
Section: биомаркеры атеросклерозаunclassified